Morphological Assessment of Vascular Anastomoses Performed Using High Frequency Electric Welding - Muzychenko,P. F (Sociedad Chilena de Anatomía, 2021)
SUMMARY: The studies of the properties of vascular structures and tissues during electric welding, in particular direct morphological changes in the blood vessel walls in the areas of welding processes, are of interest. Perforating veins, femoral veins, abdominal aorta, vena cava and porcine perforating veins of the limbs were used in this study. We performed end-to-end electric welding of the aorta, venous end-to-side electric welding, vein end-to-artery side arterial and venous welding, venous end-to-end electric welding, as well as arterial and venous lumen sealing.The results of histological studies showed the formation of a coagulated acellular protein matrix, represented by unorganized denatured protein fibrous structures. In the area of vascular tissue coagulation, lacunes were formed as a result of water evaporation from the biological tissue. In the perifocal area of the welded junction, cell reduction occurred without necrosis or charring. The data obtained confirm the safety of high frequency electric welding of the main vessels and the prospectfor clinical use of the studied techniques.